An Empirical Study on Post Investment Involvement by Indian Venture Capitalists (VCs ) - Bindiya Soni and P. K. Priyan (Abhigyan, 2013)
One of the distinguishing features of venture capital, as against the traditional forms of financing, is the active involvement by the VCs in the operations of investee companies, particularly at the strategic level. This paper focuses upon empirical analysis of post investment value addition and exit mechanism adopted by Indian VCs. The perceptions of these firms regarding their degree of involvement across various areas such as product development, marketing, general business management and finance have been analysed. Besides the value addition, monitoring and the form of control by VCs over investee companies have also been examined. Post investment phase has been extended by studying the exit decisions of these investors. Findings revealed that except the technical area, Indian VCs were highly involved in all other areas. Further, they were really meticulous about post- investment monitoring of the operations of investee companies. Regarding divestment, findings suggested that majority of investors preferred IPO over other exit routes and they would not prefer to stay invested beyond seven years.